Isolation, identification and genetic characterisation of a microsporidium isolated from the carob moth, Ectomyelois ceratoniae (Lepidoptera: Pyralidae) - Lloyd, Melissa (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2018)
Carob moth, Ectomyelois ceratoniae (Zeller) (Lepidoptera: Pyralidae) is an economically important pest, yet its biology and pest status on citrus in South Africa was, until recently, poorly understood. A study was initiated to determine the cause of collapse of a laboratory carob moth colony that was established to investigate the biology of carob moth on citrus and to develop integrated management strategies for the pest. An organism was isolated from deceased larvae and was morphologically identified as a microsporidium, based on transmission electron microscopy. Microsporidia are obligate intracellular parasites that have been found to infect almost all eukaryotes. Several Nosema species have been isolated from economically important insect pests, yet little genetic information is available from online databases for identification. Mature spores were recovered and measured using transmission electron microscopy. Spores were ovocylindrical with a wrinkled exospore, and had a length of 2.8 Â± 0.02 pm and a width of 1.6 Â± 0.04 pm. The identity of the microsporidium was confirmed by PCR amplification, sequencing and analysis of the regions encoding the ribosomal RNA. BLAST analysis of the different rRNA regions amplified showed that the microsporidium shared a 96 - 99 % identity with Nosema sp. M-Pr, Nosema carpocapsae, Nosema oulemae, Nosema sp. CO1, Microsporidium 57864, and Nosema bombi. Phylogenetic analysis of the SSU and LSU rRNA genes showed that the microsporidium clustered with the Nosema / Vairimorpha clade, supported by a bootstrap value of 100. The organisation of the RNA cistron was determined by PCR amplification using the primer set 18f and L1328r to be 5'-SSU-ITS-LSU-IGS-5S-3', which confirms the placement of the microsporidium within the Nosema / Vairimorpha clade. Because the BLAST results showed a close relationship with Nosema carpocapsae, a microsporidium infecting codling moth, the pathogenicity of the microsporidium was tested against codling moth by inoculating artificial diet with a high spore concentration of 1.1 x 107 spores/ml and a low spore concentration of 1.1 x 104 spores/ml. DNA was extracted from deceased larvae inoculated with the high concentration, and PCR of the SSU rRNA gene and bacterial 16S region was performed. Mortality in the high concentration experiment was significant (p = 0.05), but the cause of infection was determined to be a bacterium, through sequencing and BLAST analysis of the bacterial 16S rDNA. The bacterium shared a 99 % identity with Bacillus cereus. Percentage mortality (p = 0.09), larval mass (p = 0.09) and instar (p = 0.24) did not differ significantly between treatments in the low concentration experiment. DNA was extracted from the larvae and PCR amplification of the SSU rRNA gene was performed to determine whether microsporidia were present. No SSU bands were observed in any of the treatments and percentage mortality was not significant, thus it was determined that no infection occurred. This is the first study to report the genetic characterisation of a microsporidium isolated from carob moth and provides important genetic information for classification of microsporidia within the Nosema / Vairimorpha clade. It is also one of few studies in which the complete rRNA cistron of a species within the Nosema / Vairimorpha clade has been sequenced. The identification of a microsporidium from a laboratory colony of carob moth is important as it provides information about pathogens infecting the carob moth and constraints to carob moth rearing, which is useful for further studies on rearing carob moth and for establishment of a clean colony for research purposes.
Keywords: Pyralidae; Pyralidae -- Genetics; Pyralidae -- Phylogeny; Pyralidae -- Pathogens; Cladistic analysis; Transmission electron microscopy; Carob moth (Ectomyelois ceratoniae)